Keluarga Dalam Perspektif Al Qur’ān: Sebuah Kajian Tematik Tentang Konsep Keluarga - Ahmad Badrut Tamam (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2018)
Family is the earliest place for everyone to learn about everything. From the family everyone learns noble qualities, such as loyalty, mercy, and compassion, ghīrah and so on. From family life, a father or husband acquires and nurtures the nature of courage, resilience and hard work in order to defend his relatives and make him happy, whether it's his life or after his death. This is where the family concept evolves from its simplest form. Religion has a very significant role in the maturation and strengthening of the family concept, the most concrete example being contained in Islam. Given the importance of family role, this paper intends to review the concept of family in Islam, especially those contained in al-Qur'ān.